Evaluation of engineering and technology activities in primary schools in terms of learning environment, attitudes and understanding - Koul, R.; Fraser, Barry; Maynard, N.; Tade, M. (Springer, 2017)
© 2017 Springer Science+Business Media B.V., part of Springer Nature Because the importance of science, technology, engineering and mathematics (STEM) education continues to be recognised around the world, we developed and validated an instrument to assess the learning environment and student attitudes in STEM classrooms, with a specific focus on engineering and technology (E & T) activities in primary schools. When a four-scale instrument assessing classroom cooperation and involvement and student enjoyment and career interest was administered to 1095 grade 4–7 students in 36 classes in 10 schools, data analyses supported its factorial validity and reliability. When the new questionnaire and understanding scales were used to evaluate E & T activities, statistically-significant pretest–posttest changes in career interest and understanding (with large effect sizes ranging from 0.70 to 0.81 standard deviations) supported the efficacy of the instructional activities.